Pengaruh Perilaku Pedagang terhadap Upaya Pengendalian Lalat di Pasar Tradisional Kabupaten Bantaeng - La Taha, La Taha; Sulasmi, Sulasmi; Islami, Putri (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Traditional central markets still have poor sanitation. There is a lot of litter, such as vegetable scraps, plastic waste, and dirty puddles. Therefore, fly control is expected to encourage traders to change their behavior in terms of fly control. With this behavior, traders will be able to prevent diseases transmitted by flies. This study aims to determine the effect of vendor behavior on fly control. The type of research used is analytical observational research with a cross-sectional approach. The population in this study were traditional market vendors in Bantaeng Regency. The sample consisted of 46 respondents, and the data were processed using statistical analysis with a chi-square test. The results of the study based on the chi-square test showed a p-value of 0.000 < 0.05, indicating that there is an influence of knowledge on fly control in the traditional market of Bantaeng District. There is also an influence of attitude on fly control in the traditional market of Bantaeng District with a p-value of 0.006 < 0.05. There is also an influence of actions on fly control in the Traditional Market of Bantaeng District with a p-value of 0.000 < 0.05. It can be concluded that there is an influence of knowledge, attitudes, and actions on fly control. It is hoped that market managers will collaborate with health officials to provide education and guidance to vendors on the importance of maintaining environmental health.